The phenomenon of animated characters: A Generation Z perspective - Juthamongkol, Natcha; Prasertsang, Nontaporn; Pitisin, Parinda; Chandraramya, Laknara; Ingard, Apinya (Humanities, Arts and Social Sciences Studies, 2025)
This study delves into the factors contributing to the popularity of animated characters among Generation Z viewers, a generation deeply immersed in the digital transformation of entertainment and media. To unravel the allure of animated characters for Generation Z, this research explores their emotional resonance, educational significance, and cultural relevance. The research objectives encompass examining Generation Z viewers’ affinity for animated characters, utilizing a quantitative cross-sectional methodology. A sample was selected via convenience sampling, targeting animated movie enthusiasts aged 15 to 26, who participated in an online questionnaire. The study’s findings were gathered through a rigorously quality-checked questionnaire, ensuring that the measurement models for both variables, character appearance and character attributes met good quality criteria. This achievement can be attributed to the rigorous development process, which ensured content validity. The results depict a sample predominantly comprised of female university students with a pronounced penchant for animated-style movies. Their preferences lean toward 3D animation and cartoons, particularly favoring animated films segmented into parts or episodes (spin-offs). In evaluating the characters’ popularity based on appearance, male characters with endearing features, long hairstyles, superhuman abilities, and contemporary attire garnered the highest favor. Furthermore, when considering character roles, Generation Z respondents displayed a preference for main characters endowed with distinct labels, unique powers, and cheerful, sociable personalities. Characters with significant wealth also piqued their interest.